1999
DOI: 10.1183/09031936.99.13113399
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of inhaled technetium-99m-DTPA as a clinical index of pulmonary vascular disease in systemic sclerosis

Abstract: Clearance of inhaled technetium-99m-DTPA as a clinical index of pulmonary vascular disease in systemic sclerosis. O.M. Kon, Z. Daniil, C.M. Black, R.M. du Bois. #ERS Journals Ltd 1999. ABSTRACT: This study evaluated the utility of the clearance time of inhaled diethylenetriamine pentaacetate (DTPA) to distinguish pulmonary vascular disease from early fibrosing alveolitis (FA) in patients with systemic sclerosis (SSc). It was hypothesized that this would be preserved in patients with vascular disease compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Studies in humans with acute respiratory distress syndrome showed that the lung clearance correlated with the severity of the hypoxia and parenchymal lesions [6]. In patients with progressive systemic sclerosis, lung clearance was higher in fibrosing alveolitis than in pulmonary vascular disease alone, but both were increased compared to normal controls [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans with acute respiratory distress syndrome showed that the lung clearance correlated with the severity of the hypoxia and parenchymal lesions [6]. In patients with progressive systemic sclerosis, lung clearance was higher in fibrosing alveolitis than in pulmonary vascular disease alone, but both were increased compared to normal controls [7].…”
Section: Discussionmentioning
confidence: 99%
“…A possible way to measure the alveolar capillary membrane permeability is by radionuclide aerosol lung imaging. The rate of the clearance of the aerosol is inversely related to the integrity of the alveolar capillary barrier [5][6][7]. In smokers and in patients with fibrotic lung disease this integrity is disrupted causing an increased clearance of the radionuclide aerosol [8,9].…”
mentioning
confidence: 99%
“…Alveolar clearance is an index of epithelial permeability and has been used as a marker of alveolar inflammation in a number of pulmonary pathologies (17,18,19). In our experience, in non-smoking patients, alveolar clearance may be a further tool in identifying patients with a higher probability of presenting an active alveolitis.…”
Section: Discussionmentioning
confidence: 81%
“…The halftime of clearance was estimated in minutes for each lung and the average value was obtained. A clearance half-time of <40 min was regarded as abnormal and a clearance half-time of less than 20 min [50% of normal] was categorized as very rapid [5,14,15].…”
Section: Hrct In Sarcoidosis Patientsmentioning
confidence: 99%